Canonical Relations of Sensomotor Reactions of Bilateral Body Parts - Dodig, Miroslav (Advances in Social Sciences Research Journal, 2014)
The research study was carried out on a sample of 20 subjects, of male gender, from 20 to 22 years of age. An analysis was carried out in the space of sensomotor reactions of bilateral (parallel, transversal, diagonal) body parts. The measuring of sensomotor reactions in bilateral body structures was developed through an especially constructed instrumentarium (Kinesiometer, M. Dodig, 1987). The obtained results have been processed by application of canonical correlational analysis (Cooley and Lohnes,1971). Based on maximum cohesion between the pair of linear functions of variable groups that measured sensomotor reactions (transversal, parallel, diagonal) body parts, characteristic canonical roots were extracted. In the field of transversal – parallel reactions of body parts, one pair of characteristic canonical roots, which explained 85% of joint variance. In the field of parallel and diagonal body parts, two characteristic canonical roots were extracted, the first explaining 86%, while the second one 61% of joint variance. In the field of diagonal and transversal body parts, two characteristic canonical roots were extracted, the first explaining 90%, the second 72% of joint variance. The obtained results indicate a topological and functional dependency of sensomotor reactions of bilateral (transversal, parallel, and parallel) body parts. An efficiency of functioning of the emission signal speed and the speed of the synaptic transmission (the number of synaptic ties and flow through synaptic barriers), efficient functioning of commissural relations between the hemispheres and the efficiency of afferent and efferent paths directed towards sensomotor reactions of bilateral (transversal, parallel, and diagonal) body parts can probably be found at the basis of these indicators.